Enhancing Patient Safety Competence Through Virtual Simulation Training and Artificial Intelligence (ViSTA): A Quasi-Experimental Study in Samarinda - Irfan, Irfan; Sindi, Fitriani (STMIK Widya Cipta Dharma, 2025)
Patient safety is a key indicator of healthcare quality, yet it remains a critical challenge in Indonesia, including in Samarinda. The high incidence of patient safety events highlights the urgent need for innovative interventions to enhance healthcare workers’ competence. Virtual Simulation Training and Artificial Intelligence (ViSTA) is considered a potential solution to address this issue. This study aimed to evaluate the effectiveness of ViSTA in improving healthcare workers’ competence in managing patient safety incidents. A quasi-experimental design with a pre–post test and control group was employed, involving 40 healthcare workers in Samarinda. Respondents were divided into an intervention group (n=20), who participated in ViSTA training, and a control group (n=20), who received no intervention. Competence was measured before and after the intervention. Data analysis was performed using paired t-tests and independent t-tests. The intervention group demonstrated a significant improvement in competence scores after training (p<0.001), whereas the control group showed no meaningful change. Posttest comparisons between groups also revealed a significant difference (p<0.001), underscoring the effectiveness of ViSTA in enhancing healthcare workers’ skills in managing patient safety incidents. ViSTA proved to be effective in improving competence through interactive, realistic, and data-driven learning experiences. These findings support the integration of simulation technology and artificial intelligence as a sustainable training strategy, particularly in regions with limited access to face-to-face training. ViSTA holds strong potential to serve as a national training model for strengthening patient safety systems in Indonesia